2020
DOI: 10.1111/jonm.13106
|View full text |Cite
|
Sign up to set email alerts
|

The influence of spiritual leadership on the subjective well‐being of Chinese registered nurses

Abstract: Background Challenging working conditions and job characteristics can result in nurses experiencing significant workplace stress and adversity. Aim To examine how and why spiritual leadership may have a positive influence on nurses’ subjective well‐being. Method A total of 339 registered nurses from five public hospitals in Mainland China participated in this study. Hypotheses were tested using the PROCESS macro. Results Spiritual leadership influenced the subjective well‐being indirectly through workplace spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 46 publications
5
43
2
Order By: Relevance
“…In general, this study had two main conclusions: The first one reveals that ethical leadership directly and indirectly affects nurses’ happiness. Therefore, we can conclude that moral leadership affects not only the work of an individual but also the subjective wellbeing of nurses, which is in line with Yang [ 31 ], Teimouri et al, [ 25 ] and Sarwar et al, [ 22 ]. Zou et al, [ 22 ] also show the effect of spiritual leadership on the nurse’s subjective well-being [ 23 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In general, this study had two main conclusions: The first one reveals that ethical leadership directly and indirectly affects nurses’ happiness. Therefore, we can conclude that moral leadership affects not only the work of an individual but also the subjective wellbeing of nurses, which is in line with Yang [ 31 ], Teimouri et al, [ 25 ] and Sarwar et al, [ 22 ]. Zou et al, [ 22 ] also show the effect of spiritual leadership on the nurse’s subjective well-being [ 23 ].…”
Section: Discussionsupporting
confidence: 86%
“…Accordingly, personnel receive help, attention, and emotional care from their leader. Accordingly, Zou et al, [ 22 ] show the effect of spiritual leadership on the Chinese nurses’ subjective well-being [ 23 ]. Teimouri et al, [ 24 ] also confirmed the effect of ethical leadership on psychological wellbeing of employees [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we can conclude that moral leadership affects not only the work of an individual but also the subjective wellbeing of nurses, which is in line with Yang [33], Teimouri et al, [25] and Sarwar et al, [26]. Zou et al, (2020) also show the effect of spiritual leadership on the nurse's subjective well-being [24]. In this regard, the authors also conducted interviews with the nurses under study, which they also con rmed and stated that the ethical leadership style in the hospital can greatly affect their mental happiness and feeling of happiness.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, employees receive help, care, and emotional support from their leader. Accordingly, Zou et al, (2020) show the effect of spiritual leadership on the Chinese nurses subjective well-being [24]. Teimouri et al, (2018) also con rmed the effect of ethical leadership on psychological wellbeing of employees [25].…”
Section: Conservation Of Resources (Cor) Theory Suggests People Strimentioning
confidence: 94%